Формування інформаційної системи моніторингу та прогнозування технічного стану транспортних засобів - Волков, Володимир; Грицук, Ігор; Грицук, Юрій (Видавництво Львівської політехніки, 2015)
Proposed an approach to formation an information system for remote monitoring and forecasting the state of the vehicle. Formed system allows to evaluate the spectrum of operating conditions, monitoring, diagnostics and forecasting technical condition of the vehicle in the conditions of ITS.
Create an information system for monitoring and forecasting technical condition of vehicles